Risk, Attributable Fraction and Attributable Number of Cause-Specific Heat-Related Emergency Hospital Admissions in Switzerland - Schulte, Florian; Röösli, Martin; Ragettli, Martina S. (International Journal of Public Health, 2024)
Objectives. We assessed the relationship between heat and emergency hospital admissions (EHAs) in Switzerland using clinically relevant metrics.Applying distributed lag non-linear models, we investigated temperature-admission associations between May and September 1998-2019 for various disease groups, by age class and gender. We estimated the relative risk (RR) for moderate (29 °C) and extreme (34°C) daily maximum temperatures relative to disease-specific optimum temperature, and calculated attributable fractions (AFs) for hot days and the following week. We also calculated the total number of heat-related EHAs.Results. We attributed 31,387 (95% confidence interval: 21,567-40,408) EHAs to above-optimal temperatures, 1.1% (0.7-1.4%) of the total. Extreme temperatures increased the EHA risk for mental, infectious and neurological diseases. We observed particularly high AFs due to extreme heat for dehydration (85.9%, 95%CI: 82.4%-88.8%) and acute kidney injury (AKI, 56.1%, 95%CI: 45.3%-64.7%). While EHA risk generally increased with age, we also found high RRs for infectious diseases in children (0-15 years) and AKI in young adults (15-64 years).Conclusions. Hot weather increases the EHA risk in Switzerland. Therefore a comprehensive clinical and public health response is needed.